Novel Mutations in the PKD1 and PKD2 Genes of Chinese Patients with Autosomal Dominant Polycystic Kidney Disease - Dechao Xu; Yiyi Ma; Xiangchen Gu; Rongrong Bian; Yunhui Lu; Xiaohong Xing; Changlin Mei (Karger Publishers, 2018)
Background/Aims: Autosomal dominant polycystic kidney disease (ADPKD) is the most common inherited kidney disorder with mutations in PKD1 or PKD2. This study aimed to identify novel PKD1 and PKD2 mutations in Chinese patients with ADPKD. Methods: Mutational analyses of both PKD genes were performed in 120 Chinese families with inherited ADPKD using long-range PCR and targeted next-generation sequencing approaches. Sanger sequencing was performed to check the positive mutations, while multiplex ligation-dependent probe amplification was adopted to examine those without mutations for the presence of large deletions. Results: A total of 93 mutations in PKD1 and PKD2 were identified in 98 Chinese families with ADPKD inheritance and the detection rate was 81.7% (98/120). The mutation rates of PKD1 and PKD2 were 91.4% (85/93) and 8.6% (85/93), respectively. Among the 93 mutations, 59.1% (55/93) were reported for the first time. A total of 65 mutations (26 nonsense, 33 frameshift, 2 large deletion, and 4 typical splicing mutations) were identified as definite pathogenic mutations. The remaining 28 mutations (21 missense, 3 in-frame deletion, and 4 atypical splicing mutations) were determined as probable pathogenic mutations. In addition, 9 de novo mutations were found by pedigree analysis. Correlation analysis between genotype and phenotype revealed that patients with PKD1 mutations or truncating mutations exhibited the most severe clinical outcome. Conclusion: The newly identified sites for known mutations will facilitate the early diagnosis and prediction of prognosis in patients with ADPKD, and provide fundamental genetic information for clinical intervention to prevent the inheritance of this disease in affected families.